Unfavourable outcomes in maxillofacial injuries: How to avoid and manage - Atul Parashar; Ramesh Kumar Sharma (Indian Journal of Plastic Surgery)
Faciomaxillary injuries remain one of the common injuries managed by plastic surgeons. The goal of treatment in these injuries is the three-dimensional restoration of the disturbed anatomy so as to achieve pre-injury form and function. In this article, the authors review the anatomic, diagnostic and management considerations to optimise results and minimise the late post-traumatic deformities. Most of the adverse outcomes are usually a result of poorly addressed underlying structural injury during the primary management. An accurate physical examination combined with detailed computed tomographic scanning of the craniofacial skeleton is required to generate an appropriate treatment plan. This organised approach has proven effective in restoring the injured structures to pre-injury status. Multiple clinical cases are used to illustrate the different fracture patterns along with various surgical techniques to achieve an acceptable outcome. Early diagnosis and timely management of complications in these complex injuries is also discussed.